Online shopping satisfaction in Malaysia: A framework for security, trust and cybercrime - Imtiaz Ali, Najma; Samsuri, Suhaila; Abu Seman, Muhamad Sadry; Brohi, Imtiaz Ali; Shah, Asadullah (IEEE, 2016)
Customer satisfaction plays very important role in online shopping. There is always a drought on what actually drives the customer satisfaction in online shopping. Many studies have been done to understand the customer satisfaction in online shopping, however, as of now, there is no study found that have exactly define the user satisfaction through trust and security. These are the two factors that have been identified as a major barrier in customer’s satisfaction in online shopping, especially in the business to consumer B2C e-commerce mode. We also consider the cybercrime as another major barrier to achieve the customer satisfaction in online shopping. Although numerous studies have been conducted which related to the area, there is no satisfactory solution for trust and security in online shopping has been attained, therefore, in order to address this issue, we proposed a research framework that emphasize on trust and security mechanisms to achieve customer’s satisfaction. We also show the negative impact of cybercrime on customer trust and satisfaction. In this paper we present the framework that has been designed based on five essential current issues to achieve customer satisfaction in online shopping, which directly impacted the customer’s trust. The essential current issues namely are financial security, personal security, system security, privacy and cybercrime.